The dilemma of the Indian characters in K.S. Maniam's In a Far Country - Mani, Manimangai (Center for Resource, Research and Publication Services, 2018)
During the middle of 19th century whilst Malaya was still under British colonial rule, a large number of Indians migrated to Malaya as indentured laborers. They were mainly brought in by the British to work in the rubberplantations. Many of the works on early Indian diaspora highlights the hardships and sufferings these immigrants faced in the plantations. This paper will discuss the lives and struggles of the early Indian immigrants and their descendants in establishing a home and identity in Malaya. This will be based on K.S. Maniam’s novel titled In a Far Country (1991). This paper analyses thedilemma faced by the early Indian settlers in Malaya in the quest for an identity in the new land. Finally, this paper will the discuss the rejections faced by these settlers in establishing a sense of belongingness in Malaya.